Cost-effectiveness of increasing cervical cancer screening coverage in the Middle East: An example from Lebanon. Issue 4 (23rd January 2017) - Sharma, Monisha; Seoud, Muhieddine; Kim, Jane J.
Abstract: Background: Most cervical cancer (CC) cases in Lebanon are detected at later stages and associated with high mortality. There is no national organized CC screening program so screening is opportunistic and limited to women who can pay out-of-pocket. Therefore, a small percentage of women receive repeated screenings while most are under-or never screened. We evaluated the cost-effectiveness of increasing screening coverage and extending intervals. Methods: We used an individual-based Monte Carlo model simulating HPV and CC natural history and screening. We calibrated the model to epidemiological data from Lebanon, including CC incidence and HPV type distribution. We evaluated cytology and HPV DNA screening for women aged 25–65 years, varying coverage from 20 to 70% and frequency from 1 to 5 years. Results: At 20% coverage, annual cytologic screening reduced lifetime CC risk by 14% and had an incremental cost-effectiveness ratio of I$80, 670/year of life saved (YLS), far exceeding Lebanon's gross domestic product (GDP) per capita (I$17, 460), a commonly cited cost-effectiveness threshold. By comparison, increasing cytologic screening coverage to 50% and extending screening intervals to 3 and 5 years provided greater CC reduction (26.1% and 21.4, respectively) at lower costs compared to 20% coverage with annual screening. Screening every 5 years with HPV DNA testing at 50% coverage provided greater CC reductions than cytology at the same frequency (23.4%) and was cost-effective assuming a cost of I$18 per HPV test administered (I$12, 210/YLS); HPV DNA testing every 4 years at 50% coverage was also cost-effective at the same cost per test (I$16, 340). Increasing coverage of annual cytology was not found to be cost-effective. Conclusion: Current practice of repeated cytology in a small percentage of women is inefficient. Increasing coverage to 50% with extended screening intervals provides greater health benefits at a reasonable cost and can more equitably distribute health gains. Novel HPV DNA strategies offer greater CC reductions and may be more cost-effective than cytology.